Small-Scale Farmers’Perceptions of Agricultural Information Sources in Northen Haiti - Priscilla Zelaya; Amy Harder; T. Grady Roberts (Journal of International Agricultural and Extension Education, 2016)
Agricultural extension in developing countries can be a major source of support for small-scale farmers. In Haiti, the majority of the agricultural population is made up of small-scale farmers. In the past, Haiti’s extension system has suffered from various governmental instabilities in the nation. This study sought to (a) determine the information channels small-scale farmers use in the North Department of Haiti, (b) determine the accessibility of quality information as perceived by small-scale farmers in the North Department of Haiti, and (c) identify the perceivedbarriers to successful production ofsmall-scale farmers in the North Department of Haiti.Results from this study showed Haitian farmers in the North Department gain their information for farming from a variety of sources. The farmers in this study varied in their perceptions of the accessibility of quality information in the area. While some farmers participated in groups with extension services, most farmers had not participated in these groups. Farmers in this study also displayed a lack of trust towards service providers in the region. Farmer perceptions of external factors as barriers towards production illustrated a sense of powerlessness in their production practices. Recommendations include using opinion leaders to engage small-scale farmers and build trust towards service pro Agricultural extension in developing countries can be a major source of support for small-scale farmers. In Haiti, the majority of the agricultural population is made up of small-scale farmers. In the past, Haiti’s extension system has suffered from various governmental instabilities in the nation. This study sought to (a) determine the information channels small-scale farmers use in the North Department of Haiti, (b) determine the accessibility of quality information as perceived by small-scale farmers in the North Department of Haiti, and (c) identify the perceivedbarriers to successful production ofsmall-scale farmers in the North Department of Haiti.Results from this study showed Haitian farmers in the North Department gain their information for farming from a variety of sources. The farmers in this study varied in their perceptions of the accessibility of quality information in the area. While some farmers participated in groups with extension services, most farmers had not participated in these groups. Farmers in this study also displayed a lack of trust towards service providers in the region. Farmer perceptions of external factors as barriers towards production illustrated a sense of powerlessness in their production practices. Recommendations include using opinion leaders to engage small-scale farmers and build trust towards service providers.
Keywords: Haiti; Food Security; Small-Scale; Farmers; Information Soures